Multifunctional Superamphiphobic TiO2 Nanostructure Surfaces with Facile Wettability and Adhesion Engineering. Issue 23 (28th July 2014) - Huang, Jian‐Ying; Lai, Yue‐Kun; Pan, Fei; Yang, Lei; Wang, Hui; Zhang, Ke‐Qin; Fuchs, Harald; Chi, Li‐Feng
<x xml:space="preserve">Abstract</x> Compared to conventional top‐down photo‐cleavage method, a facile bottom‐up ink‐combination method to in situ and rapidly achieve water wettability and adhesion transition, with a great contrast on the superamphiphobic TiO2 nanostructured film, is described. Moreover, such combination method is suitable for various kinds of superamphiphobic substrate. Oil‐based ink covering or removing changes not only the topographical morphology but also surface chemical composition, and these resultant topographical morphology and composition engineering realize the site‐selectively switchable wettability varying from superamphiphobicity to amphiphilicity, and water adhesion between sliding superamphiphobicity and sticky superamphiphobicity in micro‐scale. Additionally, positive and negative micro‐pattern can be achieved by taking advantage of the inherent photocatalytic property of TiO2 with the assistance of anti‐UV light ink mask. Finally, the potential applications of the site‐selectively sticky superamphiphobic surface were demonstrated. In a proof‐of‐concept study, the microdroplet manipulation (storage, moving, mixing, and transfer), specific gas sensing, wettability template for positive and negative ZnO patterning, and site‐selective cell immobilization have been demonstrated. This study will give an important input to the field of advanced functional material surfaces with special wettability.